Resolvin E1 Attenuates Pulmonary Hypertension by Suppressing Wnt7a/β-Catenin Signaling. Issue 6 (December 2021) - Liu, Guizhu; Wan, Naifu; Liu, Qian; Chen, Yuqin; Cui, Hui; Wang, Yuanyang; Ren, Jiaoqi; Shen, Xia; Lu, Wenju; Yu, Ying; Shen, Yujun; Wang, Jian
Abstract : Pulmonary arterial hypertension (PAH) is a devastating disease characterized by severe pulmonary vascular wall remodeling and perivascular inflammation. Resolvin E1 (RvE1), a proresolving lipid mediator, has protective effects against various inflammatory diseases. However, the effect of RvE1 on PAH development remains to be determined. We aimed to investigate whether RvE1 has a therapeutic effect on PAH and, if so, to elucidate the molecular mechanisms underlying its effects. A hypoxia+SU5416-induced mouse model of pulmonary hypertension (PH) and an monocrotaline-induced rat model of PH were used to test therapeutic effect of RvE1. Lung tissues and plasma samples were collected from patients with PAH and rodent models to examine RvE1 production and its receptor chemerin chemokine-like receptor 1 (ChemR23) expression. We observed that RvE1 generation was reduced in the plasma of patients with idiopathic PAH and in lungs from experimental rodent models of PH. ChemR23 expression was markedly downregulated in hypoxia-exposed mouse pulmonary artery smooth muscle cells (PASMCs) and pulmonary arteries from PH rodents and patients with idiopathic PAH. RvE1 treatment alleviated experimental PH in both male and female rodents by inhibiting PASMC proliferation. Deletion of ChemR23 in vascular SMCs abolished the protective effect of RvE1 against hypoxia+SU5416-induced PAH in mice. Mechanistically, the RvE1/ChemR23 axis suppressed hypoxia-induced PASMC proliferation by inhibiting proliferative wingless-type MMTV integration site family member 7a/β-catenin signaling. Activation of ChemR23 by RvE1 diminished wingless-type MMTV integration site family member 7a expression in PASMCs by inhibiting protein kinase A-mediated Egr2 (early growth response 2) phosphorylation at Ser349. Thus, the RvE1/ChemR23 axis represses experimental PAH by modulating wingless-type MMTV integration site family member 7a/β-catenin signaling in PASMCs and may serve as a therapeutic target for the management of PAH. Abstract : Supplemental Digital Content is available in the text.